2012
DOI: 10.7196/samj.5195
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-initiation and maintenance of patients on antiretroviral therapy: Are nurses in primary care clinics initiating ART after attending NIMART training?

Abstract: Despite the remarkable achievement of the scale-up of antiretroviral therapy (ART) in South Africa over the past 7 years (about 1 million people on ART), the estimated number of people (1.2 million) requiring treatment in the next 2 years exceeds the capacity of the healthcare system if treatment continues to be initiated only by doctors. [1][2][3] In South Africa, there are 69 doctors and 388 nurses per 100 000 population.3 Task-shifting from doctors to nurses for initiating and maintaining ART is a logical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 5 publications
3
61
0
Order By: Relevance
“…Literature also indicates that infrastructural shortages largely impeded the effectiveness of the programme because of lack of operational space in the health centres. From a study that sampled nurses from the 7 provinces of South Africa, they reported that their work was impeded because they did not have a room where they could consult the patients (Cameron et al 2012). This is further supported by other findings that indicate that infrastructural challenges such as consulting rooms were also impeding the success of the NIMART programme (Nyasulu et al 2013).…”
Section: Discussion Of the Findingssupporting
confidence: 64%
See 2 more Smart Citations
“…Literature also indicates that infrastructural shortages largely impeded the effectiveness of the programme because of lack of operational space in the health centres. From a study that sampled nurses from the 7 provinces of South Africa, they reported that their work was impeded because they did not have a room where they could consult the patients (Cameron et al 2012). This is further supported by other findings that indicate that infrastructural challenges such as consulting rooms were also impeding the success of the NIMART programme (Nyasulu et al 2013).…”
Section: Discussion Of the Findingssupporting
confidence: 64%
“…The government needs to improve the working conditions to avoid the nurses leaving to western world where they are paid handsomely (Oosthuizen & Ehlers 2007;Brier 2009). To further confirm this point other findings also indicated that the fact of overworking the nurses due to being fewer in number was affecting their motivation to work and possibly their output (Cameron et al 2012) It is therefore important that workers working environment is made conducive. The government needs to understand that there is an inextricable relationship between good and conducive working conditions and productivity (Lawler 1994).…”
Section: Discussion Of the Findingsmentioning
confidence: 67%
See 1 more Smart Citation
“…Cameron and colleagues 4 found that, despites challenges, many primary care nurses working in the seven provinces surveyed have taken on the responsibility of sharing the task of initiating and maintaining HIV-positive patients on ART. To meet the targets of further ART treatment, urgent requirements are: addressing the shortage of nurses at primary care facilities; providing additional consulting rooms; further training in clinical skills and pharmacology; and expansion of clinical mentoring.…”
Section: Aids Turnaroundmentioning
confidence: 99%
“…Three papers [2][3][4] provide messages of hope for the massive task of managing South Africa's huge HIV/AIDS pandemic.…”
Section: Aids Turnaroundmentioning
confidence: 99%